Perancangan UI/UX Aplikasi Perpustakaan Digital Berbasis Web dengan Pendekatan Metode Design Thinking - Risyda, Fitria; Gardenia, Yulisa; Awaluddin, Muryan (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2025)
Today's library management increasingly demands quality and professionalism so that the resultscan be utilized to the maximum extent possible by its users. The library on the Dirgantara MarsekalSuryadarma University campus already has a website-based digital library service. This serviceis aimed at students, lecturers and the general public who need book references. However, theservices provided have limitations ranging from performance to user interface appearance. Thisresearch aims to develop a professional digital library at Dirgantara Marshal SuryadarmaUniversity. Designing the User Interface (UI) and User Experience (UX) using the Figmaapplication with a good and intuitive Design Thinking method and can meet the expectations ofthe needs of Dirgantara Marsekal Suryadarma University library users. Testing using the SingleEase Question (SEQ) method to see the level of effectiveness, efficiency and user satisfaction withthe UI/UX design prototype of the Digital Library Application that will be built. The test resultsshow a value of 6.7 on a scale of 7, indicating that the UI/UX design of the application that hasbeen designed is considered good and in accordance with user needs